A Analisis Aplikasi E-Money Berbasis Mobile untuk Transaksi Pembayaran di Dharmawangsa Foodcourt Menggunakan Metode Usability Testing - Annisa Ashari; Muhammad Eka; M. Arif Rahman (LKP Unity Academy, 2025)
Dharmawangsa Foodcourt Medan relies entirely on cash-based transactions, generating persistent operational issues including prolonged queuing, cashier miscalculation errors, and the absence of automated financial recording. This condition is inconsistent with the digital literacy profile of its primary users, namely the academic community. This study aims to design, develop, and evaluate an Android-based electronic payment application as a transaction digitalization solution within a campus foodcourt environment. System development employed the Waterfall model, encompassing requirements analysis, system design, implementation, testing, and maintenance phases. Data were gathered through field observation, structured interviews with foodcourt management and tenants, literature review, and transaction workflow documentation. System evaluation was conducted using two approaches: black-box testing to verify complete feature functionality, and usability testing based on the ISO 9241-11 standard involving 10 active users. Black-box testing confirmed that all features operated according to specifications without functional failures. Usability testing produced an overall score of 84.95%, classified as Very Good, comprising effectiveness at 86.00%, efficiency at 83.33%, and user satisfaction at 85.33%. These findings demonstrate that the developed system effectively replaces cash transactions, enhances financial recording transparency, and delivers a faster and more structured transaction experience for users within higher education foodcourt settings.